Comparison Of Emotional Intelligence of Students Who Are Active in Sports UKM And Those Who Are Not Active In Sports UKM - Muhammad Akbar Syafruddin; Agus Sutriawan (Journal Physical Health Recreation (JPHR), 2025)
This study is a comparative descriptive study that aims to compare the level of emotional intelligence of students who are active in Student Activity Units (UKM) and those who are not active in UKM. The subjects of the study were 50 students of the Faculty of Sport Science, Makassar State University, which were determined using the purposive sampling technique. Several criteria that were considered by the researcher in determining the sample were 1) students in semesters 3 to 5, 2) active in participating in the lecture process, 3) willing to participate in the research process, 4) in good health. The data collection technique was carried out using an emotional intelligence questionnaire consisting of aspects of self-awareness, self-regulation, motivation, empathy, and social skills. While the data analysis technique used was the independent sample t-test. The results of the data analysis showed that the emotional intelligence of UKM Olahraga students and non-UKM students had a Sig value of 0.001 or <0.05. So it can be said that there is a difference in data between the emotional intelligence of UKM Olaharag students and non-UKM students. Furthermore, the mean value of emotional intelligence data of UKM Olahara students is 118.88 and the mean value of emotional intelligence of non-UKM students is 116.20 so that the mean difference is 2.68. Based on the results of these tests, it can be concluded that the emotional intelligence of UKM Olahraga students is better than the emotional intelligence of non-UKM students.